Publisher´s Advertising Strategies to Widen and Diversify Readership: the Example of Bohemia - Madl, Claire (Dějiny – teorie – kritika, 2018)
The study brings a formal analysis of the advertisements published in four Prague newspapers at the end of the eighteenth century, two in German and two in Czech. It enables us to understand the way publishers used this medium and targeted new readers. The article then questions the role of the two locally used languages in publishers’ strategies and the boundaries booksellers “imagined” for their readership. In the complex sociocultural configuration of the Habsburg monarchy, they were not yet working within a fixed framework that would place boundaries on their activities or their clientele. Several elements of the advertisements enable us to distinguish different types of publishers. Until at least the 1820s, publishers’ strategies were not always defined by the language of the books they were advertising, but by other discriminatin criteria: the quality of the language used in the book, the readers’ multilingualism, the scale and structure of distribution networks, the publisher’s attitude towards tradition.